Teacher Assistance in Explaining Project-Based Learning Strategies to Improve Students' Speaking (Presentation) Skills in the Digital Era - Nurjamin, Asep; Mujizat, Tetty; Karsini, Rosi; Saputra, Budi; Rohman, Ajid Abdul; Mulyana, Dede; Nurlia, Nani; Sudrajat, Dedih; Sukaesih, Iis Abdul (Fakultas Kewirausahaan Universitas Garut, 2023)
This teacher mentoring program significantly enhanced the understanding and capabilities of teachers in Garut Regency in integrating Project-Based Learning (PBL) and digital technology to develop students' presentation skills. Key indicators of success included high teacher enthusiasm and a shift in their mindset regarding the importance of oral communication in the digital era. Active collaboration among lecturers, students, and partner teachers not only fostered innovative project designs but also ignited a new spirit in creating learning environments that empower students to speak more confidently. Thus, the program has directly contributed to improving the quality of education in Garut, equipping students with essential 21st-century communication competencies. For sustainability, strengthening long-term collaboration, providing continuous digital learning resources, and conducting further impact studies to directly measure the program's effects on students are recommended.